Respuestas
Respuesta dada por:
6
*Primero
![\frac{x}{y} = \frac{32}{4} = 8 \\ \\ x = 8y \frac{x}{y} = \frac{32}{4} = 8 \\ \\ x = 8y](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%7D%7By%7D++%3D++%5Cfrac%7B32%7D%7B4%7D++%3D+8+%5C%5C++%5C%5C+x+%3D+8y)
*Luego
![\frac{x + y}{x - y} = \frac{8y + y}{8y - y} = \frac{9y}{7y} = \frac{9}{7} \frac{x + y}{x - y} = \frac{8y + y}{8y - y} = \frac{9y}{7y} = \frac{9}{7}](https://tex.z-dn.net/?f=+%5Cfrac%7Bx+%2B+y%7D%7Bx+-+y%7D++%3D++%5Cfrac%7B8y+%2B+y%7D%7B8y+-+y%7D++%3D++%5Cfrac%7B9y%7D%7B7y%7D++%3D++%5Cfrac%7B9%7D%7B7%7D+)
La razón es 9/7
*Luego
La razón es 9/7
Vican600:
Roycross has respondido 61 preguntas populares, verdad ??
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años